American E. F. University at Beune (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1919)
The following letter has been received from Prof. Alfred C. Lane, of Tufts College, who is now in charge of the department, of mining in the College of Engineering, American E. F. University, Beaune, France. My DEAR MR. STOUGHTON: I have had a very interesting time here. We were received fast Saturday with great courtesy by the Schneiders at the Creusot plant, and saw many interesting things, from the mammoth guns clown. In one trip I saw a coal mine, an iron mine, an oilshale mine, a gypsum mine, and a most beautiful fluorspar mine. So you see we were not badly located. A mine like Epinac, which has a washery, a briquetting plant, and great central electric plant where coal that might otherwise be waste is converted into electricity and shipped away at 30,000 volts pressure, is of interest mechanically as well as geologically. Many of the French coal seams are very thick here and have especial mining methods. The Department of Mining has been manned by men with whom it was a pleasure and an honor to be associated, as well as with Dean Reber who was in charge of the College of Engineering as a whole. Names like Captain H. C. Ray, former professor at the University of Pittsburgh, on leave in the army, Captain Archbald of the Colliery Engineer at one time, whose work in the Pennsylvania coal mines is well known, Captain Vail of the Engineering and Mining Journal staff and Captain E. C. Dietrich of the Southwest, are familiar to members of the Institute, and Are guarantees of competent instruction.